A better mbs for all australians. Issue 5 (8th May 2017) - Robinson, Bruce
Abstract : Objectives: The MBS Review Taskforce is undertaking an independent clinician-led review of the Medicare Benefits Schedule (MBS). This is the first comprehensive review in 30 years of the 5700 items covered in the MBS. The priority with this review is to ensure that the items are aligned with contemporary clinical evidence and practice and improve health outcomes for all Australians. The taskforce will also seek to identify any services that may be unnecessary, outdated or potentially unsafe. The taskforce is committed to providing recommendations to government that will allow the MBS to deliver on each of these key goals: affordable and universal access; best practice health services; value for the individual patient; and value for the health system. The clinical review of MBS items, ranging from consultations, procedures and diagnostics is carried out by discipline specific clinical committees and working groups. Methods: The taskforce has asked the clinical committees to undertake the following tasks: consider whether there are items that are obsolete and should be removed from the MBS; consider identified priority reviews of selected MBS services; develop a program of work to consider the balance of MBS services within its remit and items assigned; and advise the taskforce on relevant general MBS issues identified in the course of their deliberations. Results: Committees release reports with draft recommendations and invite stakeholder feedback. The recommendations do not represent the final position on items and remain subject to consideration of stakeholder feedback and the taskforce. The taskforce will then deliver finalised recommendations to government throughout the review and deliver a final report to government at the end. To ensure the MBS remains up-to-date the taskforce will also develop an ongoing system of review after this current review is completed. Conclusions: We will report progress of the neurology clinical committee establishment.